Pengembangan Media Pembelajaran Gurita Berbasis Karakter untuk Meningkatkan Hasil Belajar Kognitif pada Materi Pengamalan Sila Pancasila Siswa Kelas IV SD - Susanti, Atika; Muktadir, Abdul (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
The purpose of this research is to produce a Character-Based Gurita Learning Media to improve the cognitive learning outcomes of fourth-grade elementary school students. Using the ADDIE development model, the study involved two media experts, two subject matter experts, one fourth-grade teacher, and 20 students from SDN 44 Kota Bengkulu. Data were collected through expert validation sheets and user feasibility questionnaires. (1) The media consists of several components: (a) octopus head, (b) octopus body, (c) octopus arms, and (d) a support pole. (2) The media received high feasibility ratings from both media experts (score of 86) and content experts (score of 67), categorized as very feasible. (3) Teacher responses also rated it highly, with scores of 87 and 85, while the average score from student responses was 12.90. (4) A paired samples t-test showed a significant improvement in student learning outcomes, with pretest scores rising from an average of 74.57 to 85.65 in the posttest, yielding a gain score of 0.44 in the moderate category. These results suggest that the Gurpensila media is highly suitable for use as a teaching aid in Pancasila Education, particularly for teaching the practice of Pancasila principles in fourth-grade elementary school.